Organic Reactions 2019
DOI: 10.1002/0471264180.or100.02
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Trapping of Functionalized Aryl‐ and Heteroarylmagnesium and ‐Zinc Compounds

Abstract: Zinc and magnesium organometallic reagents are intimately linked with the development of synthetic organic chemistry. They play a fundamental role in a vast variety of synthetic transformations used in research laboratories as well as in the chemical industry. This chapter covers the most important preparative methods for the generation of functionalized aryl‐ and heteroarylmagnesium and ‐zinc organometallic reagents. These methods, including metal insertions, halogen/metal exchanges, transmetalations and dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 263 publications
0
4
0
Order By: Relevance
“…All reactions were performed using standard Schlenk-line techniques under argon atmosphere. 48 TMPMgCl·LiCl and iPrMgCl·LiCl are commercially available (Sigma-Aldrich, Acros Organics, Albemarle, etc. ) and were as all other organometallic reagents used after titration.…”
Section: Preparative Aspectsmentioning
confidence: 99%
“…All reactions were performed using standard Schlenk-line techniques under argon atmosphere. 48 TMPMgCl·LiCl and iPrMgCl·LiCl are commercially available (Sigma-Aldrich, Acros Organics, Albemarle, etc. ) and were as all other organometallic reagents used after titration.…”
Section: Preparative Aspectsmentioning
confidence: 99%
“…These Csp 3 –Csp 3 cross-couplings are particularly difficult due to a hampered oxidative insertion of the transition-metal catalyst into the alkyl–X bond and the propensity of the subsequently formed alkyl-transition metal species to undergo β-hydride elimination. , Especially, the use of mild organometallic reagents in these couplings, such as organozinc compounds, is still a challenge . Zinc organometallics display several beneficial properties, including a high functional group compatibility and the ability to undergo a fast transmetalation to a transition-metal catalyst. , Additionally, the growing commercial availability of these reagents and the low toxicity of zinc salts make them an attractive class of metal reagents. , Various palladium- and nickel-catalyzed Csp 3 –Csp 3 cross-couplings using zinc organometallics, including enantioselective versions, have been reported by Organ, Fu, and others. ,− ,, However, the high price of palladium and the toxicity of nickel salts triggered the search for cheaper and more benign metal catalysts. Although iron, cobalt, and manganese salts have been found to catalyze the cross-coupling of alkyl halides with alkylmagnesium reagents, there is no protocol utilizing alkylzinc organometallics as coupling reagents.…”
mentioning
confidence: 99%
“…It was shown that relatively inexpensive and less toxic CoCl 2 does efficiently catalyze cross-couplings . Also, organozinc compounds are excellent nucleophilic reagents for various Co-catalyzed cross-coupling reactions, as a broad range of sensitive functional groups are tolerated in these organometallics . 1,2-Substituted alkyl halides were used as electrophiles for trans -diastereoselective cobalt-catalyzed cross-coupling reactions. ,,, ́ In preliminary experiments, the readily available α-bromolactone 1 , which was prepared from d -isoascorbic acid in 99% ee , was submitted to an arylation using 4-anisylzinc chloride ( 2a ).…”
mentioning
confidence: 99%